# |
ODE |
Mathematica |
Maple |
\[
{}3 x^{2} y+2 x^{3} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{3}+3 y^{\prime } y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}5 x y+2 y+5+2 x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y+x +2 y+1+\left (1+x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}27 x y^{2}+8 y^{3}+\left (18 x^{2} y+12 x y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}6 x y^{2}+2 y+\left (12 x^{2} y+6 x +3\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}+\left (x y^{2}+6 x y+\frac {1}{y}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}12 x^{3} y+24 x^{2} y^{2}+\left (9 x^{4}+32 x^{3} y+4 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y+4 x y+2 y+\left (x^{2}+x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}-y+\left (x^{4}-x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\cos \left (x \right ) \cos \left (y\right )+\left (\sin \left (x \right ) \cos \left (y\right )-\sin \left (x \right ) \sin \left (y\right )+y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x y+y^{2}+\left (2 x y+x^{2}-2 x^{2} y^{2}-2 x y^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \sin \left (y\right )+x \left (\sin \left (y\right )-y \cos \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}a y+b x y+\left (c x +d x y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2} y^{3}-y^{2}+y+\left (-x y+2 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y+3 \left (x^{2}+x^{2} y^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}a \cos \left (x \right ) y-y^{2} \sin \left (x \right )+\left (b \cos \left (x \right ) y-x \sin \left (x \right ) y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{4} x^{4}+x^{5} y^{3} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \left (x \cos \left (x \right )+2 \sin \left (x \right )\right )+x \left (1+y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{3} x^{4}+y+\left (x^{5} y^{2}-x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 x y+2 y^{2}+y+\left (x^{2}+2 x y+x +2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}12 x y+6 y^{3}+\left (9 x^{2}+10 x y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2} y^{2}+2 y+2 x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y^{2}+k^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y^{2}-3 y+2 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y^{2}+5 y-6 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y^{2}+8 y+7 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y^{2}+14 y+50 = 0
\] |
✓ |
✓ |
|
\[
{}6 y^{\prime }+6 y^{2}-y-1 = 0
\] |
✓ |
✓ |
|
\[
{}36 y^{\prime }+36 y^{2}-12 y+1 = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} \left (y^{\prime }+y^{2}\right )-x \left (x +2\right ) y+x +2 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y^{2}+4 x y+4 x^{2}+2 = 0
\] |
✓ |
✓ |
|
\[
{}\left (2 x +1\right ) \left (y^{\prime }+y^{2}\right )-2 y-2 x -3 = 0
\] |
✓ |
✓ |
|
\[
{}\left (3 x -1\right ) \left (y^{\prime }+y^{2}\right )-\left (3 x +2\right ) y-6 x +8 = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} \left (y^{\prime }+y^{2}\right )+x y+x^{2}-\frac {1}{4} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} \left (y^{\prime }+y^{2}\right )-7 x y+7 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\sin \left (t \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+{\mathrm e}^{t^{2}} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 t y = t
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 t y = t
\] |
✓ |
✓ |
|
\[
{}y+y^{\prime } = \frac {1}{t^{2}+1}
\] |
✓ |
✓ |
|
\[
{}\cos \left (t \right ) y+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sqrt {t}\, \sin \left (t \right ) y+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {2 t y}{t^{2}+1}+y^{\prime } = \frac {1}{t^{2}+1}
\] |
✓ |
✓ |
|
\[
{}y+y^{\prime } = {\mathrm e}^{t} t
\] |
✓ |
✓ |
|
\[
{}t^{2} y+y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}t^{2} y+y^{\prime } = t^{2}
\] |
✓ |
✓ |
|
\[
{}\frac {t y}{t^{2}+1}+y^{\prime } = 1-\frac {t^{3} y}{t^{4}+1}
\] |
✓ |
✓ |
|
\[
{}\sqrt {t^{2}+1}\, y+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sqrt {t^{2}+1}\, y \,{\mathrm e}^{-t}+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 t y = t
\] |
✓ |
✓ |
|
\[
{}t y+y^{\prime } = t +1
\] |
✓ |
✓ |
|
\[
{}y+y^{\prime } = \frac {1}{t^{2}+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 t y = 1
\] |
✓ |
✓ |
|
\[
{}t y+\left (t^{2}+1\right ) y^{\prime } = \left (t^{2}+1\right )^{{5}/{2}}
\] |
✓ |
✓ |
|
\[
{}4 t y+\left (t^{2}+1\right ) y^{\prime } = t
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{t} = \frac {1}{t^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{\sqrt {t}} = {\mathrm e}^{\frac {\sqrt {t}}{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{t} = \cos \left (t \right )+\frac {\sin \left (t \right )}{t}
\] |
✓ |
✓ |
|
\[
{}\tan \left (t \right ) y+y^{\prime } = \cos \left (t \right ) \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}\left (t^{2}+1\right ) y^{\prime } = 1+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (t +1\right ) \left (y+1\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1-t +y^{2}-t y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{3+t +y}
\] |
✓ |
✓ |
|
\[
{}\cos \left (y\right ) \sin \left (t \right ) y^{\prime } = \cos \left (t \right ) \sin \left (y\right )
\] |
✓ |
✓ |
|
\[
{}t^{2} \left (1+y^{2}\right )+2 y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 t}{y+t^{2} y}
\] |
✓ |
✓ |
|
\[
{}\sqrt {t^{2}+1}\, y^{\prime } = \frac {t y^{3}}{\sqrt {t^{2}+1}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {3 t^{2}+4 t +2}{-2+2 y}
\] |
✓ |
✓ |
|
\[
{}\cos \left (y\right ) y^{\prime } = -\frac {t \sin \left (y\right )}{t^{2}+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = k \left (a -y\right ) \left (b -y\right )
\] |
✓ |
✓ |
|
\[
{}3 t y^{\prime } = \cos \left (t \right ) y
\] |
✓ |
✓ |
|
\[
{}t y^{\prime } = y+\sqrt {t^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}2 t y y^{\prime } = 3 y^{2}-t^{2}
\] |
✓ |
✓ |
|
\[
{}\left (t -\sqrt {t y}\right ) y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y+t}{t -y}
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{\frac {t}{y}} \left (y-t \right ) y^{\prime }+y \left (1+{\mathrm e}^{\frac {t}{y}}\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {t +y+1}{t -y+3}
\] |
✓ |
✓ |
|
\[
{}1+t -2 y+\left (4 t -3 y-6\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}t +2 y+3+\left (2 t +4 y-1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t \sin \left (y\right )+{\mathrm e}^{t} y^{3}+\left (t^{2} \cos \left (y\right )+3 \,{\mathrm e}^{t} y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1+{\mathrm e}^{t y} \left (1+t y\right )+\left (1+{\mathrm e}^{t y} t^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sec \left (t \right ) \tan \left (t \right )+\sec \left (t \right )^{2} y+\left (\tan \left (t \right )+2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {y^{2}}{2}-2 \,{\mathrm e}^{t} y+\left (-{\mathrm e}^{t}+y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t y^{3}+3 t^{2} y^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t \cos \left (y\right )+3 t^{2} y+\left (t^{3}-t^{2} \sin \left (y\right )-y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 t^{2}+4 t y+\left (2 t^{2}+2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t -2 \,{\mathrm e}^{t y} \sin \left (2 t \right )+{\mathrm e}^{t y} \cos \left (2 t \right ) y+\left (-3+{\mathrm e}^{t y} t \cos \left (2 t \right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 t y+y^{2}+\left (t^{2}+t y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}+\cos \left (t^{2}\right )
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = 1+y+y^{2} \cos \left (t \right )
\] |
✗ |
✓ |
|
\[
{}y^{\prime } = t +y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{-t^{2}}+y^{2}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = {\mathrm e}^{-t^{2}}+y^{2}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = {\mathrm e}^{-t^{2}}+y^{2}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = y+{\mathrm e}^{-y}+{\mathrm e}^{-t}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = y^{3}+{\mathrm e}^{-5 t}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = {\mathrm e}^{\left (y-t \right )^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (4 y+{\mathrm e}^{-t^{2}}\right ) {\mathrm e}^{2 y}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = {\mathrm e}^{-t}+\ln \left (1+y^{2}\right )
\] |
✗ |
✗ |
|